A Method to Identify Energy Efficiency Measures for Factory Systems Based on Qualitative Modeling - Krones, Manuela (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2017)
Manuela Krones develops a method that supports factory planners in generating energy-efficient planning solutions. The method provides qualitative description concepts for factory planning tasks and energy efficiency knowledge as well as an algorithm-based linkage between these measures and the respective planning tasks. Its application is guided by a procedure model which allows a general applicability in the manufacturing sector. The results contain energy efficiency measures that are suitable for a specific planning task and reveal the roles of various actors for the measures' implementation. Contents Driving Concerns for and Barriers against Energy Efficiency Approaches to Increase Energy Efficiency in Factories Socio-Technical Description of Factory Planning Tasks Description of Energy Efficiency Measures Case Studies on Welding Processes and Logistics Systems Target Groups Lecturers and Students of Industrial Engineering, Production Engineering, Environmental Engineering, Mechanical Engineering Practitioners in Factory Planning, Production Engineering, Energy Management The Author Dr. Manuela Krones works as a research assistant at the Department of Factory Planning and Factory Management at Chemnitz University of Technology, Germany, and has conducted several projects on the energy efficiency of production and logistics systems.